Penggunaan Epiklorohidrin Dalam Meningkatkan Stabilitas Adsorben Kitosan Berikatan Silang Dan Kitosan Tercetak Ionik Kobal - Muhammad Qaddafi; Abd. Wahid Wahab; Nursiah La Nafie; Paulina Taba (Al-Kimia, 2014)
The use of epichlorohydrin to improve the stability of chitosan adsorbent has been carried out. The purpose of this study was to determine the stability of the chitosan adsorbent after modified into epichlorohydrin cross-linked chitosan and ionic cobalt imprinted adsorbent chitosan cross-linked epichlorohydrin. Adsorbent prepared by homogeneous gel formation of chitosan in acetic acid medium and then modified into epichlorohydrin cross-linked chitosan beads and ionic cobalt imprinted adsorbent chitosan cross-linked epichlorohydrin. Stability of the adsorbent was determined by calculating the percentage of insoluble material after stirring the adsorbent in nitric acid medium at pH 1, 2, and 3 for 12 hours. The results of FTIR spectra show a shift of the absorption band of chitosan were compared with epichlorohydrin cross-linked chitosan and ionic cobalt imprinted adsorbent chitosan cross-linked epichlorohydrin. The use of epichlorohydrin as cross-linked agent may increase the stability of the adsorbent to maintain the percentage of insoluble material by 89% at pH 3 for epichlorohydrin cross-linked chitosan adsorbent and 96% at pH 3 for ionic cobalt imprinted adsorbent chitosan  cross- linked epichlorohydrin.